2023
DOI: 10.1007/s00227-023-04182-8
|View full text |Cite
|
Sign up to set email alerts
|

A review of current knowledge on reproductive and larval processes of deep-sea corals

Abstract: The presence of corals living in deep waters around the globe has been documented in various publications since the late 1800s, when the first research vessels set sail on multi-year voyages. Ecological research on these species, however, only truly began some 100 years later. We now know that many species of deep-sea coral provide ecosystem services by creating complex habitat for thousands of associated species, and thus are major contributors to global marine biodiversity. Among the many vital ecological pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 136 publications
0
9
0
Order By: Relevance
“…Philopatric propagules are prevalent across many groups of sessile marine invertebrates, including poriferans and cnidarians [42,43,[73][74][75][76]. In the presence of a current, it is feasible that there could be preferential lee-side recruitment of the propagule relative to its parent, thereby producing a linear feature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Philopatric propagules are prevalent across many groups of sessile marine invertebrates, including poriferans and cnidarians [42,43,[73][74][75][76]. In the presence of a current, it is feasible that there could be preferential lee-side recruitment of the propagule relative to its parent, thereby producing a linear feature.…”
Section: Discussionmentioning
confidence: 99%
“…[41]) or capable of active swimming, have an aplanic dispersal capacity (immediate settling), and may demonstrate benthic (including parental) development [40,42]. Philopatric propagules include macroscopic buds or fragments, some embryos and larvae (often brooded or crawling [40,43]). Flow patterns around an obstacle may lead to increased settling of passive pelagic propagules in a linear fashion, or alternatively, the sequential production of philopatric propagules may interact with a current to create linear features in the lee of the parent organism.…”
Section: 'Conga Lines' and Explanations For Aligned Specimensmentioning
confidence: 99%
“… Harrison (2011) , summarized the reproductive characteristics of scleractinian corals (encompassing shallow, mesophotic and CWCs), showing that 71% of scleractinian corals are hermaphrodites, whereas 26% are gonochoric species and only 3% are showing mixed patterns. Nevertheless, despite shallow-water scleractinian corals being mostly hermaphrodites ( Fadlallah, 1983a ; Harrison & Wallace, 1990 ; Richmond & Hunter, 1990 ), most CWC scleractinians studied to date have been reported to be gonochoric ( Feehan, Waller & Häussermann, 2019 ; Waller, 2005 ; Waller & Feehan, 2013 ; Waller et al, 2023 ). The large number of hermaphroditic species found in shallow waters (which have been more investigated, mainly due to a better accessibility) originally suggested that hermaphroditism was the most ancestral reproductive condition in scleractinian corals ( Szmant, 1986 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies focusing on scleractinian reproduction, have been conducted on tropical species ( Fadlallah, 1983a ; Harrison & Wallace, 1990 ). However, reproduction studies on mesophotic ( Shlesinger & Loya, 2019 ) and CWCs have substantially increased during the last decades ( i.e ., Brooke & Järnegren, 2013 ; Feehan, Waller & Häussermann, 2019 ; Larsson et al, 2014 ; Strömberg & Larsson, 2017 ; Waller, Tyler & Gage, 2002 , 2008 ; Waller & Feehan, 2013 ; Waller & Tyler, 2005 , 2011 ; Waller et al, 2023 ). Notwithstanding, our current knowledge on the reproductive biology of scleractinians from temperate and cold waters is still scarce, in particular regarding the Mediterranean ( Goffredo et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Trawling impacts on stylasterid populations may be mitigated by their small sizes and settlement in natural refuge areas, providing multiple remnant populations to seed recovery (Clark et al, 2016a). Studies of the shallow-water New Zealand stylasterid Errina novaezelandiae demonstrate this species is capable of rapid growth rates up to 7 cm per year (Miller et al, 2004) and may therefore be hypothesised to sexually mature within several years, but growth and maturity rates of deep-sea stylasterid corals have not yet been studied (Waller et al, 2023). Given the substantial abundance increase observed on Morgue's summit, though, deep-sea stylasterids may be capable of similarly rapid growth and maturity rates relative to other deep-sea corals, aiding their capacity for recovery.…”
Section: Relating Abundance Observations To Expected Taxon Responsesmentioning
confidence: 99%